Pemenuhan Kebutuhan Perempuan Terkait Kehamilan di Kamp Pengungsi di Indonesia: Sebuah Studi Kualitatif - Nina Setiawati; Mekar Dwi Anggraeni; Meivita Dewi Purnamasari; Luciana Peppy (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: As Indonesia lies on several tectonic plates, it is often hit by natural disasters such as earthquakes. Women are included in the vulnerable group category during disaster situations, especially pregnant women. Purpose: This study aims to explore the needs of pregnant women in refugee camps after natural disasters. Methods: This is qualitative research with a phenomenological approach. The data were collected in 2019 through in-depth interviews with 9 women who were pregnant when the disaster occurred using purposive and snowball sampling techniques. The participants were refugees who were victims of the earthquake in Kalibening, Banjarnegara, Central Java, in 2018. Interview transcripts were analyzed using thematic analysis. Results: The following three themes were found and discussed: (1) the basic needs of pregnant women during a disaster situation in refugee camps, (2) comprehensive health examinations for pregnant women in disaster situations, and (3) pregnant women’s reluctance to stay in refugee camps. Conclusions: This study shows that pregnant women’s limited mobility restricts them from meeting their basic and perinatal needs in refugee camps. After natural disasters, many pregnant women experience complications during their pregnancy. Moreover, from a cultural aspect, being together with family was found to be important for pregnant women. Thus, there is a need for coordination between local governments and other stakeholders regarding the needs of pregnant women so that they can receive appropriate assistance accordingly.